2018
DOI: 10.21037/jtd.2018.06.53
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial block predicts atrial fibrillation in patients with carotid and coronary artery disease

Abstract: IAB is a predictor of new-onset AF in patients with carotid and coronary artery disease. Both carotid and coronary artery disease are associated with a higher prevalence of IAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
2
1
1
Order By: Relevance
“…16 Moreover, Alexander et al demonstrated that low P wave amplitude in lead DI was linked to new-onset AF in the ACS population. 17 In our investigation, this P wave index was not shown to be associated with long-term AF in AIS cases. In addition, when compared with PWD, PWPT in lead DII and VI, it had the lowest AUC value, sensitivity, and specificity for long-term AF.…”
Section: Discussioncontrasting
confidence: 49%
“…16 Moreover, Alexander et al demonstrated that low P wave amplitude in lead DI was linked to new-onset AF in the ACS population. 17 In our investigation, this P wave index was not shown to be associated with long-term AF in AIS cases. In addition, when compared with PWD, PWPT in lead DII and VI, it had the lowest AUC value, sensitivity, and specificity for long-term AF.…”
Section: Discussioncontrasting
confidence: 49%
“…In the present study, we found that the significant predictors of advanced IAB were the age of >80 years, left atrial enlargement (left atrial diameter of >40 mm), and BMI of >25 kg/m 2 , which supports and extends the results of previous studies. A study by Bryce Alexander et al demonstrated BMI of >30 kg/m 2 , male sex, and increased age (per 10 years increase) (OR = 1.46, 95% CI: 1.14–1.88) were significant predictors of IAB in patients with carotid and coronary artery disease ( Alexander et al, 2018 ). The Atherosclerosis Risk in Communities (ARIC) study showed that age, male sex, BMI, and systolic blood pressure were all risk factors for advanced IAB development ( O'Neal et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…Es importante mencionar que el patrón electrocardiográfico puede ser cambiante, coexistir con otras alteraciones del ritmo (en especial con FA) y/o la conducción, así como coexistir con alteraciones auriculares, en especial crecimiento y remodelación de la aurícula izquierda. El SB se asocia clínicamente, y relacionado a la FA y desincronización auriculoventricular, a evento vascular cerebral de tipo cardioembólico, por lo que en estos pacientes se debe realizar un protocolo diagnóstico que incluya estudio Holter, ecocardiograma y, cuando amerite, resonancia magnética nuclear (12)(13)(14)(15) .…”
Section: Discussionunclassified